K2SiF6:Mn4+ phosphor: recommendation for improving LO and D-CCT of the 7700K RPW-LEDs - Phu Tran Tin; Minh Tran; Van-Duc Phan; Hoang-Nam Nguyen; Thanh Trang Tran (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, we propose a new recommendation for improving lumen output (LO) and CCT deviation (D-CCT) of the 7700 K RPW-LEDs by K2SiF6:Mn4+ red phosphor. Based on Light Tool and Mat Lab simulation software, we can see that the D-CCT and LO can be improved significantly, but the CQS and CRI have a slight decrease with increasing the concentration of the red phosphor. Besides, the analytical and simulation results agree well with each other.